Sugarcane leaves-derived polyphenols alleviate metabolic syndrome and modulate gut microbiota of ob/ob mice - Li Sun; Tao Wang; Baosong Chen; Cui Guo; Shanshan Qiao; Jinghan Lin; Huan Liao; Huanqin Dai; Bin Wang; Jingzu Sun; Hongwei Liu (Food Science and Human Wellness)
Sugarcane leaves-derived polyphenols (SLP) have been demonstrated to have diverse health-promoting benefits, but the mechanism of action has not been fully elucidated. This study aimed to investigate the anti-metabolic disease effects of SLP and the underlying mechanisms in mice. In the current study, we prepared the SLP mainly consisting of three flavonoid glycosides, three phenol derivatives, and two lignans including one new compound, and further demonstrated that SLP reduced body weight gain and fat accumulation, improved glucose and lipid metabolism disorders, ameliorated hepatic steatosis, and regulated short-chain fatty acids (SCFAs) production and secondary bile acids metabolism in ob/ob mice. Notably, SLP largely altered the gut microbiota composition, especially enriching the commensal bacteria Akkermansia muciniphila and Bacteroides acidifaciens. Oral gavage with the above two strains ameliorated metabolic syndrome (MetS), regulated secondary bile acid metabolism, and increased the production of SCFAs in high-fat diet (HFD)-induced obese mice. These results demonstrated that SLP could be used as a prebiotic to attenuate MetS via regulating gut microbiota composition and further activating the secondary bile acids-mediated gut-adipose axis.